2013
DOI: 10.1155/2013/219097
|View full text |Cite
|
Sign up to set email alerts
|

Female Gender Remains an Independent Risk Factor for Poor Outcome after Acute Nontraumatic Intracerebral Hemorrhage

Abstract: Objective. To study whether gender influences outcome after intracerebral hemorrhage (ICH). Methods. Cohort study of 245 consecutive adults presenting to the emergency department with spontaneous ICH from January 2006 to December 2008. Patients with subarachnoid hemorrhage, extradural hemorrhage, and recurrence of hemorrhage were excluded. Results. There were no differences noted between genders in stroke severity (NIHSS) at presentation, ICH volume, or intraventricular extension (IVE) of hemorrhage. Despite t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 32 publications
3
41
0
Order By: Relevance
“…Most of these data have been reported previously, including the higher ICH prevalence in men, 19 although this finding is not uniform in all studies. 4 In most of the previous reports, women with ICH were older than their male counterparts, 12,18,20 similar to the findings for ischemic stroke. 21 The higher tobacco and alcohol use we observed in men also has been described previously 22 and probably reflects behavioral and cultural sex differences rather than a sex-specific risk factor.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Most of these data have been reported previously, including the higher ICH prevalence in men, 19 although this finding is not uniform in all studies. 4 In most of the previous reports, women with ICH were older than their male counterparts, 12,18,20 similar to the findings for ischemic stroke. 21 The higher tobacco and alcohol use we observed in men also has been described previously 22 and probably reflects behavioral and cultural sex differences rather than a sex-specific risk factor.…”
supporting
confidence: 78%
“…Some methodologic problems that would account for the inconsistencies and heterogeneity of the available data have been noted, such as differences in metrics used, length of study period, race/ethnicity of participants, etiology, or the adjustments made in the statistical analysis. [4][5][6] Moreover, most of the available data are from retrospective stroke registries [6][7][8][9][10][11][12] or from studies published more than a decade ago. 13,14 The most recent published series comes from Asian countries, 15,16 and probably have some bias and racial/ethnic specificity.…”
mentioning
confidence: 99%
“…11,[25][26][27] The results of our study concur with studies that found female sex to be predictive of ADL dependency after stroke. [27][28][29][30][31][32][33] In a systematic review by Gall et al, it was hypothesized that women may be more vulnerable than men to worse outcomes because of differences in demographic, social, and medical histories. 34 In the present study, women were ≈4 years older than men and a slightly higher proportion had atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were limitations, several factors which were believed to affect the outcomes, i.e. age, 30 gender, 31 GCS on admission and volume of the hematomawere comparable in both groups. 32,33 In conclusion, a single dose of 100 mg tigecycline treatment before surgical procedure for hematoma evacuation of SSICH can significantly reduce TNF-α plasma level.…”
Section: 15mentioning
confidence: 81%